2011
DOI: 10.3928/01913913-20100818-02
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Cysts as a Complication After Strabismus Surgery

Abstract: Recession may be a risk factor in the development of a conjunctival cyst caused by the high frequency of dragging Tenon capsule during this surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…[3][4][5][6] This complication has a reported incidence of 0.25% after strabismus procedures. 7 The purple/blue grayish hue of such cysts, noted in our patient, has been previously cited along with the frequent delay in growth, secondary strabismus, and clinical presentation for evaluation. 6,8 Although thermal cauterization or intralesional injection with isopropyl alcohol have been successfully used to shrink some conjunctival cysts, 9,10 these techniques do not address the large secondary incommitant strabismus associated with many giant conjunctival cysts.…”
Section: Diagnosis and Discussionsupporting
confidence: 70%
“…[3][4][5][6] This complication has a reported incidence of 0.25% after strabismus procedures. 7 The purple/blue grayish hue of such cysts, noted in our patient, has been previously cited along with the frequent delay in growth, secondary strabismus, and clinical presentation for evaluation. 6,8 Although thermal cauterization or intralesional injection with isopropyl alcohol have been successfully used to shrink some conjunctival cysts, 9,10 these techniques do not address the large secondary incommitant strabismus associated with many giant conjunctival cysts.…”
Section: Diagnosis and Discussionsupporting
confidence: 70%
“…It has been suggested that careful retraction of tissues may prevent this complication. They may disappear spontaneously, but persistent cases often require surgical excision [16]- [18]. In our case, conjunctival cyst occurred in the nasal sector four months after medial rectus recession for partially refractive accommodative esotropia.…”
Section: Discussionmentioning
confidence: 70%
“…The incidence of epithelial inclusion cysts is reported to range from 0.25% to 0.4% of strabismus surgery. 1,7 The duration to development of the cysts can range from a few days to 70 years post-operatively. 8,9 Our patient shared a similar time-frame with a previous case report series of three patients by Anjali et al who reported the appearance of cyst at 2 -4 months.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our case corresponded to reported literature where it was reported rectus recessions were associated with an increased incidence of cyst formation. 7 Treatment of Figure 5: Macroscopic appearance of excised cyst with cyst wall intact the cyst intraoperatively conjunctival epithelial inclusion cysts can be divided into non-surgical and surgical options. A trial of steroids is the first-line treatment as some cysts may resolve spontaneously.…”
Section: Discussionmentioning
confidence: 99%